Kinetics of photocatalytic degradation of atrazine on molecularly imprinted titania film. Issue 3 (4th May 2012) - Zhang, Chunjing; Yang, Zhengpeng; Zhang, Chunxiao; Sun, Yukun
ABSTRACT A titania film imprinted by atrazine molecule at the surface of a quartz crystal was prepared using molecular imprinting and surface sol–gel process. The quartz crystal microbalance technique was employed to in situ investigate the degradation behavior of atrazine on the molecularly imprinted titania film. The obtained results reveal that the molecular imprinting can enhance degradation of atrazine on titania films, and the degradation rate constants (K) estimated from the in situ frequency measurement is about 0.62 × 10−3 s−1, which is two times higher than that obtained on non‐imprinted titania films. © 2012 Curtin University of Technology and John Wiley & Sons, Ltd.